Embryo Development and Chick Performance of Local Chicken Following In-Ovo Injection of L-Arginine Into Local Chicken Eggs - Muhammad Taufik; Urfiana Sara; Muhammad Yusuf; Fatma Maruddin; Muhammad Azhar (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
This study aims to determine the effect of in-ovo injection of L-arginine into local chicken eggs on embryo development and chick performance of local chicken. A total of 160 eggs were incubated using semi-automatic incubator with temperature of 37-38C and relative humidity of 55-65%. The injected L-arginine solution has a concentration of 0.5% (m/v). In treatment was divided into 4 groups, the first treatment was without injection (control), the second treatment was the injection of 0.2 mL L-arginine solution 0.5% (m/v)/egg, the third treatment was the injection of 0.4 mL L-arginine solution. 0.5% (m/v)/egg, and fourth treatment was the injection of L-arginine solution 0.6 mL 0.5%(m/v)/egg. The results showed that embryo mortality and hatchability were lower with L-arginine injection treatment than without injection. All treatments showed no effect on extraembryonic fluid absorption, but there was an increase in embryo weight in the injection treatment 0.2, 0.4, 0.6 mL L-Arginine 0.5% /eggs 2,355 g, 2,577 g, 2,705, respectively. In conclusion, an in-ovo injection of L-arginine in local chicken eggs has a good effect (the beneficial effect) on embryo death and embryo performance. Injection of 0.4 ml L-Arginine 0.5% /eggs improved hatchability and Newly Hatched Chick Weight (NHCW).